A realistic reading as a feminist tool: The Prodigal Son as a case study - Toit, Charel D. du (HTS teologiese studies, 2022)
The parables of Jesus have historically been attributed with a plethora of interpretations. The first hearers of the parables of Jesus had native (emic) knowledge of the social realities embedded in the parables told by Jesus, that is, cultural scripts present in the parables that might not be apparent to modern readers. Because of this, the modern reader of a parable might not be aware of all the different cultural scripts in a given parable, especially if these scripts are not specifically mentioned or explained by the gospel narrators. Using the parable of the Prodigal Son as an example, this study argues that there are voices in the parable most probably heard by its first hearers that modern hearers might not be aware of. These ‘muted’ voices not heard by modern readers of the parables often include the voices of women and other minority figures. In this study, a case is made for the possible value that a ‘realistic reading’ of familial parables could bring to the interpretation of the parables.Contribution: It is suggested that this reading can contribute to feminist biblical scholarship’s deconstruction and reconstruction of gender paradigms of Christian theology if the voices of women are ‘exhumed’ from or ‘unhidden’ within, patriarchal and androcentric texts.